Presentation of Costs and Incomes of Budgetary Units in Accordance with Polish Accounting Regulations - Rudnicka, Bożena (Prezentacja przychodów i kosztów jednostek budżetowych zgodnie z polskimi przepisami rachunkowymi, 2010)
Specific rules of accounting concerning budgetary units do no define the idea of costs and incomes in different manner than it is in the Accounting Act. However, they affect registry rules of those costs and their presentation in profit and loss account, imposing, among other things, obligation of registering operating costs by kinds and preparing a comparative variant of profit and loss account, with separation in that account of incomes from budgetary titles included in budgetary revenues of local government units and costs composed not only of costs of units activity, but also of titles of benefits for private persons financed from the budget and expenditures related to functionality of executive organs of local government. The model of a profit and loss account valid for budgetary units is often criticized for being not specific enough in showing costs and incomes of those entities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 159-168
Keywords: budgetary unit; specific accounting rules; operational costs; profit and loss ac-count